META ANALISIS KEEFEKTIFAN INQUIRY BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS PEMBELAJARAN TEMATIK SEKOLAH DASAR - Adhi Susanto; Endang Indarini (JGK (Jurnal Guru Kita), 2022)
Critical thinking is one of the abilities that must be possessed by students. One of the preferred learning models in the implementation of the 2013 Curriculum is the inquiry learning model (Inquiry Based Learning). The purpose of this study was to test the effectiveness of the inquiry-based learning model in improving students' critical thinking skills from thematic learning in elementary schools in published experimental research using the meta-analysis method. The data analysis technique used is ancova test and effect size. The articles used were published in 2016-2021. The results of the analysis show that the significance value for the Inquiry Based Learning variable is 0.000. Because the value of Sig. < 0.05 then H_o is rejected. This shows that at the 95% confidence level it can be said that there is a linear relationship between Inquiry Based Learning and the critical thinking skills acquired by students. The results of the analysis using the random effect model show that there is a significant positive correlation between the application of the Inquiry-Based Learning model and critical thinking skills. Researchers suggest to complement the results of this study in improving students' critical thinking skills with other learning models in accordance with the latest process standards from the Ministry of Education and Culture.